Analytic Solutions For Integro-Differential Inequalities Using Modified Adomian Decomposition Method - Abdul Razzaq, Emane Abdul Lateef; Yassein, Samaher Marez (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This paper applies the Modified Adomian Decomposition Method (MADM) for solving Integro-Differential Inequality, this method  is one of effective to construct analytic approximate solutions for linear and nonlinear integro-differential inequalities without solving many integrals and transformed or discretization. Several examples are presented, the analytic results show that this method is a promising and powerful for solving these problems.